Breast Cancer Patients’ Perceptions of Their Experience With Chemotherapy-Induced Nausea and Vomiting and Its Impact on Quality of Life in Jeddah, Saudi Arabia - Ilyas, Ahmed B (Cureus, 2020)
Background Breast cancer accounts for 11.6% of all neoplasms worldwide and is the commonest cancer among Saudi females (29.7%). Chemotherapy-induced nausea and vomiting (CINV) is a very common side effect of chemotherapy that has a great impact on the quality of life (QoL) of patients. Literature is still scarce about this effect on the Saudi population. This study aims to explore breast cancer patients’ perception of their experience with CINV and its impact on QoL. Methods This is a cross-sectional retrospective study conducted on Saudi adult female breast cancer patients who underwent chemotherapy at King Abdulaziz Medical City, Jeddah, Saudi Arabia. Data collected through patients’ records review, face-to-face and telephone structured interviews using a questionnaire composed of four parts: sociodemographic characteristics, nature of acute CINV (within 24 hours) and delayed CINV (after 24 hours), impact on QoL, and general information on their experience. Results Out of a total population of 173, 98 (56.65%) patients participated in the study. The main findings show that 78.6% experienced nausea, whereas 35.7% experienced vomiting. Most participants had a moderate-to-extreme impact on their QoL due to nausea (74.0%) and vomiting (62.9%). Overall, 57.5% rated anti-emetics as excellent for controlling CINV, whereas 22.9% rated them as moderate to good; 83.5% were completely compliant on anti-emetics and 71.1% reported that they received completely comprehensive education about CINV. Religious practices (74.4%), diet (57.7%), and relaxation techniques (44.9%) were found to be the most common non-pharmacological methods used to control CINV. No significant correlation was found between the effect of CINV on QoL and sociodemographic characteristics (p > 0.05). Conclusions CINV is very common among Saudi adult female breast cancer patients; despite being completely compliant and receiving comprehensive education and effective anti-emetics; CINV still had a high impact on different aspects of QoL. Health care professionals should consider CINV as an issue and should find effective strategies for alleviating patients’ suffering.